Enterprise information architecture: Empirical evidence to support Zachman Framework in Malaysia - Md Dahalin, Zulkhairi; Abd Razak, Rafidah; Dahari@Damiri, Rohaya; Kamaruddin, Siti Sakira; Abdullah, Sahadah (Faculty of Information Technology, Universiti Utara Malaysia, 2006)
The paper aims to describe findings based on a research study on current Enterprise Information Architecture (EIA) implementation in Malaysia. Ten enterprises from public and private sectors were chosen for case study analysis. The Zachman Framework was chosen as a guideline to assess the current practice of EIA in five of these enterprises. The study found that certain aspects of the framework were nor addressed at all, whilst other aspects that were addressed vary in terms of the different perspectives. The paper highlights gaps in the current practice and provides recommendations and suggestions for enterprises to consciously embark on the EIA paradigm in order to better align the whole enterprise to the goals of the enferprise.